MODERASI ISLAM DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Hidayat, Tatang; Abdussalam, Aam; Istianah, Istianah (Program Studi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2023)
The purpose of this study is to describe the moderation of Islam in the study of Islamic religious education. This research uses a qualitative approach and a literature study method. Based on the results of the study, Islamic teachings are radical in the sense that all of their teachings and practices are rooted in a solid belief system. The more radical the understanding and practice of religion, the softer and more it guarantees good for all. Al-Qur'an expresses Islamic moderation in the language of